The Influence of Participative Leadership on Enhancing Employee Motivation and Performance at the Regional Research and Development Planning Agency (BAPPEDA) of Wakatobi Regency, Southeast Sulawesi Province - Zuldiana, Zuldiana; Rizaldi, Andi Risfan; Akib, Muhammad (Dinasti Publisher, 2025)
Participative leadership has an important role in improving employee motivation and performance, especially in government organizations. This study aims to analyze the effect of participative leadership on employee motivation and performance at the Regional Research and Development Planning Agency (Bappeda) of Wakatobi Regency. In addition, this study also examines whether motivation acts as a mediating variable in the relationship between participative leadership and employee performance. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to employees of Bappeda Wakatobi Regency and analyzed using multiple linear regression techniques and mediation analysis. The results showed that participative leadership has a positive and significant effect on employee motivation. In addition, participative leadership also has a direct effect on employee performance. Employee motivation is proven to have a mediating role in the relationship between participative leadership and employee performance. This finding indicates that effective implementation of participative leadership can increase employee motivation, which in turn contributes to improving their performance. Therefore, government organizations need to implement more participative leadership strategies to create a more collaborative and productive work environment.